FAKTOR YANG MEMENGARUHI KEPUTUSAN KONSUMEN MENONTON PROGRAM ACARA DJARUM INDONESIA SUPER LEAGUE DI ANTV DI PROVINSI LAMPUNG - Hatta, Holila; Ardhita, Fajri (Prosiding Seminar Nasional INDOCOMPAC)
This study discusses the influence of sports programs to the consumer's decision to watch broadcast television, television programs that were subjected to experiments in this study were television program Djarum Indonesia Super League which was broadcast by a ANTV. The purpose of this study was to determine whether the attributes of programs that include relative advantage, compatibility, complexity, and observability can influence consumer decisions to watch a television broadcast simultaneously and partial, as well as to determine variable attributes of programs that have the most dominant influence on purchase decisions. This type of research study is a causal effect with the techniques of data analysis using quantitative descriptive analysis and statistical analysis. While the methods of data collection using survey methods with random sampling method of deployment. The population in this study is the whole people of Indonesia who ever watched the broadcast Djarum Indonesia Super League, represented by the sample population in this questionnaire, in which sampling was conducted by questionnaire in Lampung Province by 100 respondents. Test equipment used to test the instrument in this study is to test the reliability and validity, and hypothesis testing using multiple linear regression analysis using SPSS software version 20.0 for Windows. F test results for the fourth variable, namely the study relative advantage, compatibility, complexity, and observability in the television program, showed that all four variables together (simultaneously) has significant and positive influence on consumer decisions television. While the t test results in this study indicate that the variable relative advantage, compatibility, complexity and observability is also positive and significant influence on consumer decision watching television programs. Keywords: Television programs, relative advantage, compatibility, complexity, observability, and purchase decision.